Genetic variations of acidity in grape berries are controlled by the interplay between organic acids and potassium - Duchêne, Éric; Dumas, Vincent; Butterlin, Gisèle; Jaegli, Nathalie; Rustenholz, Camille; Chauveau, Aurélie; Bérard, Aurélie; Le Paslier, Marie Christine; Gaillard, Isabelle; Merdinoglu, Didier (Theoretical and applied genetics, 2020)
Key message In a grapevine segregating population, genomic regions governing berry pH were identified, paving the way for breeding new grapevine varieties best adapted to a warming climate. As a consequence of global warming, grapevine berry acidity is expected to dramatically decrease. Adapting grapevine ( Vitis vinifera L.) varieties to the climatic conditions of the future requires a better understanding of the genetic architecture of acidity-related traits. For this purpose, we studied during five growing seasons 120 individuals from a grapevine biparental cross. Each offspring was genotyped by simple sequence repeats markers and by hybridization on a 20-K Grapevine Illumina ® SNP chip. Quantitative trait loci (QTLs) for pH colocalized with QTLs for the ratio between potassium and tartaric acid concentrations, on chromosomes 10, 11 and 13. Strong QTLs for malic acid concentration or for the malic acid-to-tartaric acid ratio, on chromosomes 6 and 8, were not associated with variations of pH but can be useful for controlling pH stability under high temperatures. Our study highlights the interdependency between acidity parameters and consequently the constraints and degrees of freedom for designing grapevine genotypes better adapted to the expected warmer climatic conditions. In particular, it is possible to create grapevine genotypes with a high berry acidity as the result of both high tartaric acid concentrations and low K + accumulation capacities.